Sleep health challenges among women: insomnia across the lifespan - Benge, Elizabeth; Pavlova, Milena; Javaheri, Sogol (Frontiers in Sleep, 2024)
The presentation of sleep disorders varies widely among women and men, and sleep disorders among women are frequently subject to under-and delayed diagnosis. Insomnia is a complex sleep disorder with a multifactorial etiology, and women face many sex-specific sleep health challenges that may contribute to and influence the presence of insomnia symptoms across their lifespan. These include sex differences in neurobiology, hormonal variation during menstruation, pregnancy and menopause, increased prevalence of mood disorders, increased vulnerability to adverse socioeconomic factors, and gender discrimination, among other psychosocial stressors, particularly among women of racial-ethnic minority. As the medical community continues to recognize the significance of sleep as a vital pillar of overall well-being, the integration of sex-specific considerations in research, diagnosis, and treatment strategies is essential to optimizing sleep health for women.